Cow Milk Consumption Increases Iodine Status in Women of Childbearing Age in a Randomized Controlled Trial. Issue 3 (12th March 2018) - O'Kane, S Maria; Pourshahidi, L Kirsty; Mulhern, Maria S; Strain, JJ; Mackle, Emer M; Koca, Duygu; Schomburg, Lutz; Hill, Sarah; O'Reilly, Jennifer; Kmiotek, Diana; Deitrich, Christian; Bath, Sarah C; et al.
Abstract: Background: Recent evidence has highlighted the prevalence of mild-to-moderate iodine deficiency in women of childbearing age and pregnant women, with important public health ramifications due to the role of iodine, which is required for thyroid hormone production, in neurodevelopment. Cow milk contributes the greatest amount to iodine intakes in several countries. Objective: The objective of this study was to investigate the effect of increased cow milk consumption on iodine status, thyroid hormone concentrations, and selenium status. Methods: A 12-wk randomized controlled trial was conducted in 78 low–moderate milk-consuming (<250 mL/d) healthy women (aged 18–45 y). The intervention group was asked to consume 3 L semiskimmed milk/wk, whereas the control group continued their usual milk consumption (baseline median: 140 mL/d; IQR: 40–240 mL/d). At baseline and weeks 6 and 12, participants provided a spot urine sample [urinary iodine concentration (UIC), creatinine] and a fasting blood sample (thyroid hormone concentrations, serum total selenium, selenoprotein P). Results: At baseline, the median (IQR) UIC of all participants was 78.5 µg/L (39.1–126.1 µg/L). Changes in the median UIC from baseline to week 6 (35.4 compared with 0.6 µg/L; P = 0.014) and week 12 (51.6 compared with –3.8 µg/L; P = 0.045) were significantly greater in the intervention group compared with the control group. However, despite being higher within the intervention group at weeks 6 and 12, the change in the iodine:creatinine ratio from baseline was not significantly different between groups at either week 6 ( P = 0.637) or week 12 ( P = 0.178). There were no significant differences in thyroid hormone concentrations or selenium status between groups at any time point. Conclusions: The present study shows that the consumption of additional cow milk can significantly increase UIC in women of childbearing age. These results suggest that cow milk is a potentially important dietary source of iodine in this population group. This trial was registered at www.clinicaltrials.gov as NCT02767167.